2000
DOI: 10.1046/j.1464-410x.2000.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Stilboestrol plus adrenal suppression as salvage treatment for patients failing treatment with luteinizing hormone‐releasing hormone analogues and orchidectomy

Abstract: Objective To investigate the ef®cacy of low-dose stilboestrol (SB) with hydrocortisone in patients with advanced prostate cancer refractory to androgen suppression. Patients and methods Thirty-four consecutive patients (median age 70 years, range 51±83) with metastatic disease who progressed on hormone therapy, as shown by recurrent/worsening symptoms and an increase in prostate-speci®c antigen (PSA) level, were recruited and discontinued hormonal treatment before starting SB. Patients received SB (1 mg/day) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 14 publications
1
27
0
1
Order By: Relevance
“…Responses have been seen to steroids and estrogens (Farrugia et al, 2000;Nishimura et al, 2000), and chemotherapy has shown a survival advantage for these patients (Petrylak et al, 2004;Tannock et al, 2004). Until recently, it has been a universal practice to continue androgen deprivation during chemotherapy, despite previous progression on this treatment.…”
mentioning
confidence: 99%
“…Responses have been seen to steroids and estrogens (Farrugia et al, 2000;Nishimura et al, 2000), and chemotherapy has shown a survival advantage for these patients (Petrylak et al, 2004;Tannock et al, 2004). Until recently, it has been a universal practice to continue androgen deprivation during chemotherapy, despite previous progression on this treatment.…”
mentioning
confidence: 99%
“…More recently, there is evidence that some patients with 'hormone-resistant' disease (i.e. after primary androgen ablation and addition and withdrawal of a peripheral antiandrogen) may have transient responses to estrogens such as diethylstilbestrol (Farrugia et al, 2000;Orlando et al, 2000). The mechanism is unknown, but this effect might also account for responses to the agent PC-SPES, which contains phytoestrogens, that have been reported for patients with 'hormone-resistant' disease (Small et al, 2000a).…”
Section: Estrogensmentioning
confidence: 99%
“…Corticosteroids may be the treatment of choice in less ambulatory patients who have a short life expectancy, although they also have an accepted role in antitumour treatment effects. [26][27][28] Most patients will be started on 4 mg dexamethasone daily, even though there are no established evidence-based guidelines for doses of corticosteroids. 29 Other symptoms include nausea and constipation, both of which can be effectively treated by a variety of antiemetics and laxatives, respectively.…”
Section: Gastrointestinal Symptomsmentioning
confidence: 99%